Attitude of People in Coimbatore City towards Multinational Corporations - Kumar, R.Vijay; Khan, Feroz (Indian Journal of Marketing, 2004)
Multinational Corporations (MNCs) are primary actors on the world scene. Multinational Corporations view the world, not any given nation, as the arena for their actions. MNCs produce and export goods, they exploit and import natural resources and transfer intermediate goods and partially assembled components. The economic dominance of the multinationals is manifested by the fact that the MNCs control between a quarter and a third of all world production and the local sales of their foreign affiliates is about the same as the Gross National Product (GNP) of all developing countries excluding oil-exporting developing countries. Large and small, rich and poor nations welcome positive and productive actions by multinational corporations operating within their territories. In order to make use of the available resources in the most efficient manner, generate employment opportunities; reducing the trade balances and increasing the exports from India and also to encourage the inflow of foreign investments, India has also been permuting the functioning of the MNCs in India. Moreover, the MNCs realize that India is the biggest market for their products and they have been showing their interest towards the entry into India. Hence, this study examines the attitude of people in Coimbatore district towards the MNCs.